Pembagian Hand Sanitizer Berbahan Dasar Kitosan Kulit Udang Sebagai Upaya Pencegahan Penyebaran COVID-19 Di Kabupaten Pulau Morotai - Rinto M Nur; Djainudin Alwi; Nurafni Nurafni; Kismanto Koroy; Iswandi Wahab; Hartati Kapita; Titien Sofiati; Abdul Rahim Jafar; Sartika Do. Kader; Asy’ari Asy’ari (Journal Of Khairun Community Services, 2021)
The outbreak of Corona Virus Disease 2019 (COVID-19) in many countries is increasingly troubling the community. The number of COVID-19 cases in Indonesia continues to increase, including in North Maluku. The virus that causes COVID-19 is transmitted through direct hand touch, communication, and other fluid exchanges. Various efforts are being made to reduce the spread of this disease. One of the COVID-19 prevention efforts carried out is the use of hand sanitizer. Hand sanitizers generally contain 62% alcohol, softeners, and moisturizers. The benefits of hand sanitizer made from shrimp skin chitosan can microbiologically prevent bacteria, fungi, and viruses that affect the health of the skin and body. The purpose of this activity is to answer community unrest faced by the scarcity of hand sanitizer products in the market and help prevent the transmission of COVID-19 around the Morotai community. The manufacture of hand sanitizer is carried out at the FPIK Unipas Morotai Laboratory. On March 23, 2020, hand sanitizer distribution in Unipas Morotai Campus Environment, City Park, Imam Lastori Port, and Morotai Police Office Environment. Based on the results of this Community Service activity, hand sanitizer is available to the community. It is expected that this activity can be helpful to support people who do not have access to handwashing with water and soap at all times